List of non‐EU phytoplasmas of tuber‐forming Solanum spp. (23rd December 2020) - ,; Bragard, Claude; Dehnen‐Schmutz, Katharina; Gonthier, Paolo; Jaques Miret, Josep Anton; Justesen, Annemarie Fejer; MacLeod, Alan; Magnusson, Christer Sven; Milonas, Panagiotis; Navas‐Cortes, Juan A; Parnell, Stephen; Potting, Roel; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Plant Health prepared a list of non‐EU phytoplasmas of tuber‐forming Solanum spp. A systematic literature review and search of databases identified 12 phytoplasmas infecting S. tuberosum . These phytoplasmas were assigned to three categories. The first group (a) consists of seven non‐EU phytoplasmas, known to occur only outside the EU (' Candidatus Phytoplasma americanum', ' Ca . P. australiense', ' Ca . P. fragariae'‐related strain (YN‐169, YN‐10G) and ' Ca . P. hispanicum') or having only limited presence in the EU (' Ca . P. aurantifolia'–related strains, ' Ca . P. pruni'‐related strains and ' Ca . P. trifolii'). The second group (b) consists of three phytoplasmas originally described or reported from the EU. The third group (c) consists of two phytoplasmas with substantial presence in the EU, whose presence in S. tuberosum is not fully supported by the available literature. Phytoplasmas of categories (b) and (c) were excluded at this stage from further categorisation efforts. Three phytoplasmas from category (a) (' Ca . P. australiense', ' Ca . P. hispanicum' and ' Ca . P. trifolii') were excluded from further categorisation, as a pest categorisation has already been performed by EFSA. Comments provided by the EU Member States were integrated in the opinion. The main uncertainties of this listing concern: the taxonomy, the geographic distribution and prevalence and host range. The following phytoplasmas considered as non‐EU and whose presence in S. tuberosum is fully supported by literature (category (a)) are categorised by the Panel in a separate opinion: ' Ca . P. americanum', ' Ca . P. fragariae'‐related strain (YN‐169, YN‐10G), ' Ca . P. aurantifolia'–related strains and ' Ca . P. pruni'‐related strains.